Pengaruh Hasil Belajar Siswa Terhadap Pembelajaran PAI di SDN 17 Bilah Barat Menggunakan Metode Demonstrasi - Muhammad Raya Elfanda Rambe; Rahmat Idris Hasibuan (Jurnal Budi Pekerti Agama Islam, 2024)
This research aims to improve PAI learning using the demonstration method at SDN 17 Bilah Barat. This type of research is classroom action research. Action research is a type of research used in the classroom to solve learning problems with the aim of improving the quality of learning. Journal analysis of the results of this literature review uses the critical assessment method. research result. The conclusion that can be drawn is that the demonstration method can be an effective method in improving PAI learning, especially in helping students understand and apply difficult concepts. However, it should be noted that the demonstration method must be used wisely and in the right context to ensure its effectiveness in improving PAI learning.